Board diversity and stakeholder management: the moderating impact of boards' learning environment. Issue 2 (4th February 2019) - Fernandez, Whitney Douglas; Thams, Yannick
Abstract : Purpose: This paper aims to draw on insights from team learning theory and stakeholder theory to examine the influence of board composition on firms' stakeholder management practices. The authors posit that board diversity is likely to enhance stakeholder management by shaping organizational goals by placing emphasis on the interests of a wide variety of stakeholders and providing firms with relevant knowledge to enhance their ability manage these interests. The authors further theorize on the moderating role of boards' learning environment, which they conceptualized as an important complementary governance-related factor, likely to further boards' ability to enhance stakeholder management. Design/methodology/approach: The authors test these predictions using the generalized estimating equations (GEE) technique on a panel of S&P 500 firms observed from 2001 to 2011. Findings: The findings provide evidence that more diverse boards in terms of gender, nationality and race/ethnicity are generally associated with more effective stakeholder management. Further, the findings also suggest that boards' co-working experience moderates the relationship between gender and national diversity and stakeholder management. Originality/value: While corporate governance research surveys many strategic implications of board composition, limited attention has been paid to the interplay of board characteristics with stakeholder management. This study is among the first to the authors' knowledge to explore the impact of board diversity on stakeholder management using team learning research, thus drawing attention to the role of boards' co-working experience in shaping their ability to impact firms' outcomes.